Conducting a maternal near-miss case review cycle at hospital level : improving the quality of maternal and perinatal health care : manual with practical tools (World Health Organization Regional Office for Europe, 2016)
This manual explains how effectively implement the individual near-miss case review (NMCR) cycle. It is designed for hospital staff involved in maternal and newborn health care, programme managers and policy-makers who are responsible for the quality of perinatal health care at ministries of health or in facilities supporting improvement of maternal and perinatal health. The NMCR cycle is defined as a continuous quality improvement process that seeks to improve patient care and outcomes by the review of the care provided to maternal near-miss cases (defined as women who survived severe complications during pregnancy, childbirth or within 42 days of termina-tion of pregnancy). In the NMCR cycle, maternal near-miss cases are selected, typically on a monthly basis, among case managed at hospital level, and the hospital staff involved in the case management systematically evaluates the care provided against evidence-based guidelines, local protocols and standards of care. The aim is not to solve the single near-miss case under review, but rather to use the case to critically discuss local case management, procedures and attitudes, and to identify areas that can be further improved. The emphasis of the NMCR cycle is on identifying areas amenable of improvement, and finding and implementing solutions to the problems identified, with a bottom-up approach so that to ensure local ownership of the process, together with facilitating team-building dynamics. The ultimate primary purpose of the NMCR is to reduce preventable mater-nal and perinatal morbidity and mortality.
Keywords: porodnice; Quality of Health Care; Obstetric Labor Complications; Hospitals, Maternity; perinatální péče; veřejné zdravotnictví; téměř pochybení ve zdravotní péči; Perinatal Care; gynekologie a porodnictví; komplikace porodu; Near Miss, Healthcare; kvalita zdravotní péče